Benign breast disease in women of Hazara Division - Riyaz, Anila; Naeem, Shagufta; Naz, Shabana; Iqbal, Toqueer; Nadeem, Seema; Jamil, Aysha (Pakistan Journal of Physiology, 2019)
Background: Benign breast diseases are much common than malignancy however not all of them are reported. The most alarming symptoms that are investigated include breast lumps and bloody nipple discharge while other symptoms like mastalgia and skin induration are commonly ignored by the patients or treated medically. Hence the true incidence of breast diseases is much higher than recorded. In this study the frequency of various benign breast diseases occurring in Hazara division are studied. Methods: This was a retrospective study of breast biopsy specimens received over a period of five years from June 2012 to June 2017 at Histopathology Department at Ayub Teaching Hospital, Abbottabad. All cases diagnosed with ductal carcinoma-in-situ (DCIS), malignancies and lesions in the male breast were excluded from this study. The data was analyzed using SPSS-19. Results: Benign breast disease was diagnosed in 188 (59%) of the total 317 cases. The ages of patients ranged from 13–75 years with a mean age of 29±13 years. The most common lesion was fibroadenoma present in 97 (51%) followed by inflammatory lesions and then fibrocystic disease. Conclusion: Benign breast disease, although more frequent, remains under reported as patients do not seek medical help unless the symptoms are problematic. Fibroadenoma was the most frequent lesion occurring in the second decade.